Supplementation with Vitamins C and E and Exercise-Induced Delayed-Onset Muscle Soreness: A Systematic Review - María F. Torre; María Martinez-Ferran; Néstor Vallecillo; Sergio L. Jiménez; Carlos Romero-Morales; Helios Pareja-Galeano (MDPI AG, 2021)
Muscle damage induced by exercise may have several consequences such as delayed-onset muscle soreness, a side-effect of the release of free radicals during oxidative stress. To mitigate the oxidative stress cascade, the oral intake of antioxidants has been assessed by several research groups. This review examines whether supplementation with vitamin C and/or vitamin E is able to prevent or attenuate delayed-onset muscle soreness after eccentric exercise. The PubMed, Web of Science, Medline, and Embase databases were searched to identify studies meeting the inclusion criteria: primary randomized control trials, healthy male and female participants aged 16-80 years, and an intervention consisting of the intake of vitamin C and/or vitamin E without other supplements plus a controlled eccentric exercise regimen. Further requirements were the measurement of muscle soreness or markers of delayed-onset muscle soreness. All original full-text articles in English or translated into English published from January 2000 to June 2020 were considered for this review. Fourteen studies were finally identified, including 280 participants, 230 men, and 50 women aged 16-30 years. All participants were healthy individuals with different starting levels of physical activity. Supplementation was acute in two studies and chronic in 12, and its consisted of vitamin C in eight studies, vitamin E in two studies, and both in four studies. Only in 3 of the 14 studies was muscle soreness found to be significantly reduced in response to vitamin C and/or vitamin E supplementation at all time points when compared to the placebo group. Despite some studies showing the beneficial effects of chronic supplementation with these vitamins on muscle soreness manifesting 24-72 h after eccentric exercise, the evidence is so far insufficient to confirm that the intake of antioxidant vitamins is able to minimize delayed-onset muscle soreness in this context.